Early Diagnosis of Hip Dysplasia – A Stress-Radiographic Study - Madsen, J. S.; Svalastoga, E. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Presently, the diagnosis of hip dysplasia is based on a single pelvic radiographic examination of the dog at the age of 12 to 24 months. However, by this method, only a static appearance of the coxofemoral joint is evaluated. The purpose of our study was to diagnose hip dysplasia in young dogs and consequently, we included a radiographic evaluation of the dynamic appearance of the coxofemoral joint.A stress-radiographic examination was applied to 23 German Shepherd Dogs at the age of six and 12 months to obtain maximal reduction and maximal dislocation of the coxofemoral joint. Finally, at the age of 12 months, the hips were examined radiographically using the conventional criteria for hip dysplasia.At the age of six months, dogs with hip dysplasia showed significantly greater joint laxity and lateral dislocation of the femoral head than normal dogs. However, some predysplastic dogs, with lateral dislocation of the femoral head, developed normal hips and would be approved for breeding. Based on these findings, we conclude that stress-radiographic examinations of young dogs provide important, hitherto unrecognized, information of relevance in the future screening programmes to reduce the incidence of hip dysplasia.A stress-radiographic examination of young dogs provides important, hitherto unrecognized, information of relevance in the future screening programmes to reduce the incidence of hip dysplasia.
Keywords: Hip dysplasia; diagnosis; stress-radiographic examination